The Consumption Effects of Population Concentration - Zhengyu Cai; Yu Yan (Global Labor Organization (GLO), 2025)
This paper empirically examines the causal effects of population concentration on household consumption in China and explores the underlying mechanisms. After addressing endogeneity concerns from various sources, our results show that a 1% increase in urban population density leads to a 0.43 percentage point increase in household average propensity to consume and a 59.73 yuan increase in per capita consumption expenditure. Mechanism analysis reveals that, beyond the effects of urban income premiums, population density reduces consumption transaction costs and enhances social interactions, both of which encourage higher consumption. Additionally, population density raises non-housing consumption among some households by driving up housing prices.
Keywords: R12; R23; D12; 330; population density; household consumption; transaction costs; social interactions; housing prices